Book Review: The Value of an Archaeological Open-Air Museum is in its Use by Roeland Paardekooper - Ronan O’Flaherty (EXARC, 2014)
Question: What has 40,000 legs, likes to tell stories and pops up all over Europe? Answer: An archaeological open-air museum. OK, not the most brilliant riddle in the world, but the point is that with publication of Dr Paardekooper’s monograph we now, finally, have a secure databank of facts and figures relating to archaeological open-air museums in Europe, including management structures, key financial indicators, visitor profiles and visitor numbers (average of 20,000 visitors a year per site, hence those 40,000 busy little feet).